Surgical fear and sleep quality effect the postoperative quality of recovery in patients undergoing brain tumor surgery: cross sectional study - Özge Çimen; Yeliz Sürme (Perioperative Medicine)
Abstract Background Patients with a brain tumor experience high levels of anxiety because of the fear of remaining functional and neuropsychological sequelae. This situation affects the postoperative quality of recovery. This study was conducted to determine the effect of surgical fear and sleep quality on the postoperative quality of recovery and pain. Method This cross-sectional study was completed with 101 patients who met the inclusion criteria and underwent craniotomy under general anesthesia for a brain tumor between October 2020 and August 2021 in a university hospital. The data were collected using the Patient Information Form, Surgical Fear Scale, Richard Champell Sleep Scale, Quality of Recovery Questionnaire, and Patient Follow-up Form. Hierarchical regression analysis was used to reveal the determinants of postoperative quality of recovery. Results The mean fear of surgery score of women was higher than men, and sleep quality and postoperative quality of recovery were lower than men (p = 0.045). A moderate negative correlation between fear of surgery and sleep quality was found (r = -0.377; p = 0.000). There was a weak negative correlation between fear of surgery and postoperative recovery quality (r = -0.252; p = 0.011), and a weak positive correlation between preoperative sleep quality and recovery quality (r = 0.297; p = 0.003). The variables of fear, sleep, duration of hospital stay, pain, and age were found to be statistically the best predictors of postoperative quality of recovery (R2 = 0.295; p = 0.000). Conclusion As a result, surgical fear, sleep deprivation, and pain during the perioperative period negatively impact recovery quality and prolong the healing process. Psychological preparation by starting from the pre-operative period, providing sleep and rest, evaluation, and management of postoperative pain would contribute to the early recovery and discharge of patients.